2018
DOI: 10.1188/18.cjon.e103-e114
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab Vedotin: A Nursing Perspective on Best Practices and Management of Associated Adverse Events

Abstract: Peripheral neuropathy was the most common BV-associated AE across clinical trials. Other clinically relevant AEs included neutropenia, infection, and infusion-related reactions. Awareness of and preparedness for these common BV-associated AEs and other less common but significant AEs will help nurse clinicians and patients maximize the clinical benefit for patients receiving BV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The MTD of PSMA ADC compares favorably with the recommended ADCETRIS® dose of 1.8 mg/kg every 3 weeks and with the MTD range of 1.0‐2.4 mg/kg every 3 weeks reported for polatuzumab vedotin, another MMAE‐based ADC . For PSMA ADC, reductions in neutrophil counts were generally transient and self‐resolving or responsive to treatment with granulocyte colony‐stimulating factors . Prior or ongoing peripheral neuropathy is prevalent in post‐docetaxel subjects.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The MTD of PSMA ADC compares favorably with the recommended ADCETRIS® dose of 1.8 mg/kg every 3 weeks and with the MTD range of 1.0‐2.4 mg/kg every 3 weeks reported for polatuzumab vedotin, another MMAE‐based ADC . For PSMA ADC, reductions in neutrophil counts were generally transient and self‐resolving or responsive to treatment with granulocyte colony‐stimulating factors . Prior or ongoing peripheral neuropathy is prevalent in post‐docetaxel subjects.…”
Section: Discussionmentioning
confidence: 65%
“…45 For PSMA ADC, reductions in neutrophil counts were generally transient and self-resolving or responsive to treatment with granulocyte colonystimulating factors. 46 Prior or ongoing peripheral neuropathy is prevalent in post-docetaxel subjects. In this study, peripheral neuropathy was observed in a subset of subjects and was typically delayed in onset.…”
Section: Discussionmentioning
confidence: 99%
“…TNSn, which is calculated from five of the seven items in the TNSc, can be considered as a reliable, alternative, and objective clinical assessment where strength and reflex testing is removed. It can be useful if a more extended neurologic examination is not possible, as it can be done by a trained healthcare professional involved in the multidisciplinary approach of BVIN [ 103 , 104 , 109 , 110 ]. Very recently, the cut-off values for a relevant change defined as minimal clinical important difference (MCID) of TNS have been reported [ 104 ], supporting TNS implementation in clinical trials of patients treated with BV.…”
Section: Early Diagnosis and Management Of Bvinmentioning
confidence: 99%
“…Throughout treatment, patients should be monitored for signs and symptoms of neurotoxicity. By encouraging open communication and speaking with patients and caregivers about the possibility of BVIN onset and the benefits of early symptom reporting, BV adherence and effective management of PN may improve [ 103 , 109 ]. Having expertise relevant to BVIN management should form part of nurses or assistant physicians’ routine practice with patients with HL.…”
Section: Early Diagnosis and Management Of Bvinmentioning
confidence: 99%
See 1 more Smart Citation